A missed case of hereditary hemorrhagic telangiectasia: A case report - Jia Zhang; Gaoyun Pan; Yingying Zou; Xiaoshu Chen; Jingye Pan; Yi Wang; Shichao Quan; He Zou (SAGE Open Medical Case Reports, 2022)
Hereditary hemorrhagic telangiectasia is a rare autosomal dominant disorder characterized by abnormal blood vessel formation. When an abnormal vascular architecture affects the lungs and central nervous system, serious complications can occur. We report a missed case of hereditary hemorrhagic telangiectasia with pulmonary arteriovenous malformations and cerebral arteriovenous malformations. A 22-year-old Chinese female was taken to the emergency room because of unconsciousness. Emergency head contrast-enhanced computed tomography and transthoracic contrast echocardiography showed that she had cerebral arteriovenous malformations and pulmonary arteriovenous malformations. The patient experienced multiple spontaneous epistaxis since childhood, for which she was treated at a local hospital for a brief period. Her mother also had pulmonary arteriovenous malformations. The patient was diagnosed with hereditary hemorrhagic telangiectasia according to the consensus Curaçao diagnostic criteria and eventually died of hereditary hemorrhagic telangiectasia. The case report highlights the importance of early diagnosis and intervention for hereditary hemorrhagic telangiectasia. Given that hereditary hemorrhagic telangiectasia is frequently undiagnosed, increasing the physician’s awareness of hereditary hemorrhagic telangiectasia can play an important role in the timely diagnosis and treatment of these patients.